Comparison of Post-operative Mean Pain Score with Intravenous Ketorolac Versus Ibuprofen Infusion in Patients Undergoing Open Cholecystectomy Under General Anesthesia - Jalil-Ur-Rehman Butt, Riffat Saeed, Amer Latif, Tariq Ali Bangash, Zia Us Salam Qazi, Saeeda Rana (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Postoperative pain management is a key to enhanced recovery after surgery. Ketorolac and ibuprofen are both recommended by food and drug administration for this purpose, however; it is unclear, if there is any difference in the effectiveness of these drugs. Objective: To compare the post-operative mean pain score with intravenous ketorolac versus ibuprofen infusion in patients undergoing open cholecystectomy under general anesthesia. Study Design: Randomized controlled trial. Place and Duration of Study: Shaikh Zayed Hospital, Lahore from 12th January 2021 till 11th July 2021. Methodology: One hundred patients who met the inclusion criteria and assigned them randomly into two groups, each comprising 50 individuals. Before the surgery, patients in group A received IV ketorolac, while those in group B received IV ibuprofen, after which cholecystectomy was performed. We evaluated the postoperative VAS pain scores at 6 hours and analyzed the results statistically. Results: The average age of patients in the IV ketorolac group was 40±9.85 years, while those in the IV ibuprofen group had an average age of 41±9.95 years. The mean VAS pain score 6 hours after surgery was 3±0.57 for the IV ketorolac group and 4±0.91 for the IV ibuprofen group (p=0.007). Conclusion: Patients who underwent open cholecystectomy, preoperative IV administration of ketorolac resulted in a significantly greater reduction in postoperative pain scores compared to IV ibuprofen. Keywords: Analgesia, Cholecystectomy, Gallbladder